Logistical and structural challenges are the major obstacles for family medicine physicians' ability to administer adult vaccines - Ozlem Equils; Caitlyn Kellogg; Lucy Baden; Wendy Berger; Shannon Connolly (Taylor & Francis Group, 2019)
Purpose: This study was conducted to characterize the vaccination practices and challenges of family medicine physicians in Los Angeles County, California. Methods: The Los Angeles Academy of Family Physicians (LA AFP) sent out electronic surveys to all of their active members (N = 1121) between December 2017 and January 2018, and asked them to answer questions about themselves, their practice, their patient population, and their immunization practices and challenges. We then analyzed the results through basic statistical calculations and Pearson's chi-squared tests. Results: Seventy-four people (6.6%) responded to the survey, and 75% of responders stated that they administer all Advisory Committee on Immunization Practices (ACIP) recommended vaccines. The lowest vaccine administration rates were for the high-dose influenza vaccine, which 66.2% (n = 49) of respondents reported to administer, followed by the meningococcal B vaccine (68.9%; n = 51). The respondents who belonged to practices with more than 11 providers, were part of a large hospital or healthcare system, had electronic medical records (EMRs), and used the California Immunization Registry (CAIR) were more likely to report to vaccinate. The number one responding physician-reported challenge to vaccination was limited time and resources to address patient resistance followed by vaccine cost and lack of infrastructure to store vaccines. Conclusions: In this pilot study, structural and logistical challenges appeared to make the biggest impact on adult vaccination for the responding family medicine physicians. Solutions addressing these challenges will help improve the adult immunization rates.